Effect of the immersion in 1-metylciclopropene on the physicochemical and physiological properties of yellow pitahaya fruit (selenicereus megalanthus how) with minimum processing (2011)
Yellow pitahaya (Selenicereus megalanthus How), is an exotic fruit with great commercial potential, it has been commercialized without using methods that add value and/or prolong its shelf-life. The effect the application of 200 mg/lt 1-MCP on the respiratory rate and quality properties of vacuum sealed minimally processed yellow pitahaya slices during shelf-life under refrigeration was evaluated. Soluble solids, total titratable acidity, weig%t loss, total sugars, firmness and color were measured in fruit slices with and without skin. The application of 1-MCP before storage increased the respiratory rate and consequently increased soluble solids and total sugars, and did not show any detrimental on weight loss, total titratable acidity, color c%anges and firmness. and amp;owever, t%e application of 1-MCP reduced loss of vitamin C in yellow pitahaya slices with and without skin during storage time.